Investigation of the PD-1/PD-L1 Expression in the Lesional Skins of Patients with Psoriasis - Emre, Selma; Süngü, Nuran; Hayran, Yıldız; Demirseren, D Deniz; Aktaş, Akın; Özkara Duman, Tuce (Dermatology Practical & Conceptual, 2023)
Introduction: Psoriasis is an immune-mediated, chronic and inflammatory disease whose pathogenesis is affected by the interactions of several immune cells and cytokines. PD-1 is an inhibitor receptor that is expressed to a large extent in T lymphocytes and responsible for regulating autoimmunity and self-tolerance. Objectives: In this study, we aimed to investigate the expression of PD-1/PD-L molecules in the lesioned skins of psoriasis patients. Methods: The study included 30 psoriasis patients, and 15 healthy volunteers as the control group. Anti PD-1 and PD-L1 antibodies were applied to the skin biopsy samples that were collected from the patient and control groups. Cytoplasmic and membranous staining of PD-1 and PD-L1 were considered positive. The number of stained immune cells that was examined for each case. Results: The percentage of the tissues with high PD-1 (+) and PDL-1 (+) immune cell counts were significantly higher in the psoriasis patients compared to healthy controls (P values = 0.004 and 0.002, respectively). A negative and statistically significant correlation was detected between PDL-1(+) immune cell numbers and PASI scores (P = 0.033, r=-0.57). Conclusions: In the lesioned skin samples of psoriasis patients, the PD-1 and PD-L1 expressions were significantly higher in immune cells than that in the skin samples of the healthy controls. This study was the first investigation of the expression of PD-1/PD-L molecules in the immune cells in found the lesioned skins of psoriasis patients.